SURVEY ON THE SITUATION OF KOREAN LANGUAGE AND KOREAN STUDIES EDUCATION IN VIETNAM - Bac, Cao Thi Hai; Yen, Le Hai (VNU Journal of Foreign Studies, 2022)
Using the method of sociological research by questionnaire, this study made a survey on the situation of the education of Korean language and Korean studies conducted in various universities and colleges throughout Vietnam. Three main survey contents are about teaching staff, learners’ situation and education purpose. The research results partly reflect the general picture as well as the specificity of Korean language education and Korean studiesof the Northern, Central, and Southern regions in Vietnam.